ANALISIS VARIABEL MAKRO EKONOMI TERHADAP PEMBIAYAAN BERMASALAH PADA BPRS DI INDONESIA PERIODE 2014-2021 - septiatin, Aziz; Riduwansyah, Riduwansyah; Krisdayanti, Helisia (Islamic Economics Program, Faculty of Islamic Economics and Business, 2022)
In making investments, financing from Islamic banking is still the mainstay of various parties. Not all financing disbursed to the public are categorized as healthy, but some of them are financing that has poor quality or problems such as non-current financing, financing whose debtors do not meet the promised requirements, and the financing does not comply with the installment schedule. This study aims to analyze the effect of the BI Rate, Exchange Rate and Inflation on the level of non-performing financing (NPF) at Islamic Rural Banks for the period 2014-2021 per month. The method used in this research is descriptive with a quantitative approach and uses multiple linear regression analysis and hypothesis testing using the t test and F test which previously tested the classical assumptions first. The results showed that the BI Rate, exchange rate and inflation variables simultaneously had no effect on the NPF level. While partially the BI rate and inflation variables have no effect on the NPF while the exchange rate variable has a significant effect on the NPF. Keyword : BI Rate, exchange rate, Inflation, NPF